Smoke optical properties: lidar observations in Cyprus during 2021-2023 - Poutli, Maria; Hadjimitsis, Diofantos; Nisantzi, Argyro; Ansmann, Albert; Mamouri, Rodanthi-Elisavet (My University, 2024)
Climate change has affected many aspects of our lives with wildfires being one of the most important. The uncontrolled fires that occur mainly in rural or sparsely populated areas can be considered as a natural part of many ecosystems, but the changes in global climate and global warming have notably influenced their frequency and heightened risk. Smoke particles can strongly affect the climate system, by absorbing solar radiation and by influencing the evolution of clouds. Therefore, it is of great importance to investigate their optical properties. In this study we focus on the statistical analysis of smoke optical properties at different aging levels. The smoke layers were observed in the free troposphere of Limassol, Cyprus, in the summer of the period 2021-2023. Emphasis is given to the intense activity of wildfires in Turkey's Mediterranean Region in July and August 2021 as well as in the Evros region, Greece, during the summer of 2023. The analysis was performed utilizing data from the multiwavelength polarization Raman lidar, PollyXT, which is operated at the Cyprus Atmospheric Remote Sensing Observatory of the Eratosthenes Centre of Excellence at Limassol. Backward trajectories, generated with the HYSPLIT model, synergistically with VIIRS data were used to confirm the presence and the origin of smoke layers above Limassol’s site. Based on the time that smoke travelled in the atmosphere above Limassol, we characterized the various cases as fresh smoke (travel time of smoke: ≤ 1day) or non-fresh smoke (travel time: ≥ 2 days). In most cases of fresh smoke layers, the particle depolarization ratio at 532 nm (7% -18%) exceeded that of nonfresh smoke (2% -10%), suggesting soil dust influence from fires or other sources. This trend was observed at both wavelengths, with 355 nm exhibiting a more complex situation. The lidar ratio values ranged approximately from 40 to 90 sr for both fresh and non-fresh cases at both wavelengths. The POLIPHON method was also applied to estimate the vertically resolved smoke mass concentration.
Keywords: wildfires; remote sensing; lidar; optical properties; POLIPHON